CURCUMIN AS A FITONUTRIENT OF FOOD PLANT RAW MATERIALS, HAVING ANTI-QUANCED AND HYPOGLYCEMIC ACTIVITY - Irina Dmitrievna Konovalova; Ekaterina Nikolaevna Kholodova; Timur Shamil’evich Shaltumaev (Современная наука и инновации, 2022)
Currently, special attention is paid to chemoprotectors (adjuvants) of plant origin contained in plant raw materials and enhancing the clinical effectiveness of an ticancer drugs. Oneis curcumin Curcuma bread, with the aim of obtaining the product afunctional orientation. The evaluation of the new functional product on 6 indicators. The resulting products are characterized by a large volume, well-developed porosity and selective functional action.